Small GTPase regulation of GPCR anterograde trafficking - Wang, Guansong (2011)
The physiological functions of heterotrimeric G protein-coupled receptors (GPCRs) are dictated by their intracellular trafficking and precise targeting to the functional destinations. Over the past decades, most studies on the trafficking of GPCRs have focused on the events involved in endocytosis and recycling. In contrast, the molecular mechanisms underlying anterograde transport of newly synthesized GPCRs from the endoplasmic reticulum (ER) to the cell surface have just begun to be revealed. In this review, we will discuss current advances in understanding the role of Ras-like GTPases, specifically the Rab and Sar1/ARF subfamilies, in regulating cell-surface transport of GPCRs en route from the ER and the Golgi.